PENINGKATAN KEMAMPUAN MEMBACA MELALUI MEDIA KARTU KATA BERGAMBAR DENGAN STRATEGI PEMBELAJARAN INKUIRI PADA SISWA KELAS II UPTD SD INPRES MALAFAI - Ngadha, Christina; Kaka, Pelipus Wungo; Sayangan, Yohanes Vianey; Laksana, Dek Ngurah Laba (JRPD (Jurnal Riset Pendidikan Dasar), 2025)
This study aims to determine the improvement of reading ability through the media of picture word cards with inquiry learning strategies in grade II students of UPTD SD Inpres Malafai. This type of research is classroom action research (PTK) which consists of three components, namely 1) planning, 2) action and observation and, 3) reflection which in implementation and observation are carried out simultaneously. The subjects in this study are 12 students in grade II UPTD SD Inpres Malafai. The object of this research is to improve reading ability through the media of picture word cards with inquiry learning strategies. The data collection method uses the test method. The instrument used is a test question. The data in this study was analyzed using quantitative descriptive statistics. The results of this study showed that after the administration of actions for two cycles, the average score of the test results for the use of picture card media with the Inquiry approach strategy to improve reading ability in grade II students of UPTD SD Inpres Malafai increased. In the first cycle, an average score of 60, a percentage of 60%, was at the criteria of sufficient and classically or the number of students who completed as many as 5 people was 41.57%. In the second cycle, an average score of 75.83% was obtained at the sufficient criterion and classically increased to 83.33%. Thus, it can be concluded that the application of pictorial word card media with inquiry teaching strategies can improve the reading ability of grade II students of UPTD SD Inpres Malafai classically by 41.76%.